﻿The effect of formaldehyde solution in pitfall traps on the probability of catching woodlice (Isopoda, Oniscidea) - Tuf, Ivan Hadrián; Novotná, Lucie; Fryčka, Pavel (ZooKeys, 2025)
Pitfall traps containing a fixative solution are commonly used by ecologists to study ground-dwelling invertebrates. The effect of the solution on the animals being caught is a frequent topic of studies. Our study compares the effect of formaldehyde solution, water, and the random probability of catch simulated by using dry traps. Ninety pitfall traps were placed in a floodplain forest ground: one-third used 4% formaldehyde solution as a fixative, one-third used water, and one-third was left without any liquid to simulate the random probability of a catch. A layer of dry wood chips was used in the dry traps to reduce predation between the caught animals. The traps were placed in the field between April and May 2022 and emptied twice a week. Both the numbers of animals and the species caught were found to be significantly affected by the fixative solution in use. Significantly more woodlice were caught in traps filled with water; these traps also attracted significantly more Porcelliumconspersum and Trachelipusrathkii compared to the dry traps. Average day temperature and the order the traps were checked (i.e. date) had an influence on the animals caught as well. Additional laboratory experiments with Porcellioscaber confirmed that terrestrial isopods avoid formaldehyde pitfall traps more than those with water.
Keywords: Barber traps; trapability; epigeic invertebrates; terrestrial isopods; model species; epigeon